2018
DOI: 10.1007/s13365-018-0693-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection renders brain vascular pericytes susceptible to the extracellular glutamate

Abstract: Reduced pericytes coverage of endothelium in brain is one of the structural changes leading to breach of the Blood Brain Barrier during HIV infection. We previously showed in central memory T (TCM) cells that HIV latency increases cellular susceptibility to DNA damage. In this study we investigated susceptibility of primary brain pericytes infected with HIV-1 to DNA damage in response to glutamate and TNFα, both known to induce neuronal death during chronic inflammatory conditions. To infect pericytes, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Our group reported that brain pericytes express the main HIV‐1 receptor, CD4, HIV‐1 co‐receptors CCR5 and CXCR4, and that these cells are prone to HIV‐1 infection 19 . Several studies confirmed these results, identifying brain pericytes as an important player in HIV‐1 infection 11,20,22,23,44 . We recently proposed that pericytes might be HIV‐1 reservoir cells in the CNS, as they can alternate from productive HIV‐1 infection to latent steps of the viral cycle 22 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our group reported that brain pericytes express the main HIV‐1 receptor, CD4, HIV‐1 co‐receptors CCR5 and CXCR4, and that these cells are prone to HIV‐1 infection 19 . Several studies confirmed these results, identifying brain pericytes as an important player in HIV‐1 infection 11,20,22,23,44 . We recently proposed that pericytes might be HIV‐1 reservoir cells in the CNS, as they can alternate from productive HIV‐1 infection to latent steps of the viral cycle 22 .…”
Section: Discussionmentioning
confidence: 88%
“…19 Several studies confirmed these results, identifying brain pericytes as an important player in HIV-1 infection. 11,20,22,23,44 We recently proposed that pericytes might be HIV-1 reservoir cells in the CNS, as they can alternate from productive HIV-1 infection to latent steps of the viral cycle. 22 The importance of these findings stems from the fact that infection of pericytes may provide a gateway for HIV-1 to enter brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid expressing vesicular stomatitis G protein (VSV‐G) was obtained from Dr. Dykes 46 . The virus stocks were generated as described previously with some modifications 47,48 . Briefly, human embryonic kidney cells, 293T, were cotransfected with 40 μg each of NL4‐3 vector and VSV‐G vector using polyethyleneimine.…”
Section: Methodsmentioning
confidence: 99%
“…46 The virus stocks were generated as described previously with some modifications. 47,48 Briefly, human embryonic kidney cells, 293T, were cotransfected with 40 g each of NL4-3 vector and VSV-G vector using polyethyleneimine. Virus supernatant was harvested after 72 h and concentrated using PEG6000 as described and resuspended in PBS.…”
Section: Generation Of Hiv-1 Virus Stockmentioning
confidence: 99%
“…Several studies have shown that after an initial HIV infection, increased BBB permeability arises, contributing to significant neurological implications [ 17 , 18 ]. Part of this permeability change may be due to a reduction in pericyte coverage of the brain endothelium that may lead to monocyte neuro-infiltration, including trafficking of HIV-infected cells, and to elevated levels of proinflammatory cytokines [ 19 ]. Additionally, dysfunction of the BBB has been confirmed in the form of pericyte loss, contributing to the HIV-induced BBB dysregulation and associated comorbidities [ 20 ].…”
Section: The Landscape Of Hiv Infection In the Cnsmentioning
confidence: 99%